Trânsitos da masculinidade negra à nordestina e o tornar-se negro e gay em Imperatriz/ Maranhão - MORAIS, Marcos Madjer Souza (2024)
The objective of this dissertation is to analyze the intersectional subjectivities of specific social agents who are, in this case, black and gay men who reside in Imperatriz, a city in the state of Maranhão. The main focus of the work is to understand the way in which they project their same-sex relationships, in terms of choosing their sexual and romantic partners. The city of Imperatriz serves as the backdrop for the analyzes carried out in this work. Thus, the analysis of this work is based on a main premise which is that of race, in the case of racism, which intersects with other means of oppression, such as gender, with regard to the demands of masculinity, and sexuality, in relation to homophobia. Thus, among the authors used as a theoretical framework, it is worth highlighting the presence of: Neusa Santos Souza, Raweyn Connell, Patricia Hill Collins and bell hooks. The main objective of the research is to understand the experiences of each interviewee regarding their affective-sexual relationships, and how racism, homophobia and masculinity affect their bonds with other partners, whether they are just sexual or of a loving nature. Analyze, from the epistemological field of intersectionality, the joint action of each mechanism of oppression. The methodology used in the research was ethnographic, participant observation and qualitative research. The fieldwork involved interviews with 12 participants, and visits to three bars in the city, Pub Fitcion, Casarão Bar and Esquina Bar. Nighttime entertainment spaces in the city, where members of the LGBTQIAPN+ community circulate. It was found, through the interviewees' reports, that they see racism as a preponderant factor of neglect, contributing to the lack of lasting relationships. In this way, the epistemological collaboration of intersectionality stands out as an analytical tool for understanding the experiences of each participant, understanding their experiences from the semantic scenario that addressed their self-recognition as black, the acceptance of their homosexuality, and the way in which masculinity repressed his sexuality.